2020
DOI: 10.1021/acs.jpclett.0c01698
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Furin Protease Binding to SARS-CoV-2 Spike Glycoprotein and Implications for Potential Targets and Virulence

Abstract: The COVID-19 pandemic is an urgent global health emergency, and the presence of Furin site in the SARS-CoV-2 spike glycoprotein alters virulence and warrants further molecular, structural, and biophysical studies. Here we report the structure of Furin in complex with SARS-CoV-2 spike glycoprotein, demonstrating how Furin binds to the S1/S2 region of spike glycoprotein and eventually cleaves the viral protein using experimental functional studies, molecular dynamics, and docking. The structural studies underlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…In coronaviruses, membrane fusion is known to depend on proteolytic cleavage at multiple sites, including the S1/S2 site, located at the interface between the S1 and S2 domains, and the S2’ site located within the S2 domain. These cleavage events can impact infection—in fact, a distinct furin cleavage site present in the SARS-CoV-2 S1/S2 site is not found in SARS-CoV (Vankadari, 2020), and it is thought to increase infectivity through enhanced membrane fusion activity (Walls et al, 2020; Vankadari, 2020; Xia et al, 2020). Consequently, mutations at these sites can alter virulence—for instance, a recent study reported that mutations disrupting the multibasic nature of the S1/S2 site affect SARS-CoV-2 membrane fusion and entry into human lung cells (Hoffmann et al, 2020).…”
Section: Whole-genome Association Analysis Of the Sars-cov-2 Genomesmentioning
confidence: 99%
“…In coronaviruses, membrane fusion is known to depend on proteolytic cleavage at multiple sites, including the S1/S2 site, located at the interface between the S1 and S2 domains, and the S2’ site located within the S2 domain. These cleavage events can impact infection—in fact, a distinct furin cleavage site present in the SARS-CoV-2 S1/S2 site is not found in SARS-CoV (Vankadari, 2020), and it is thought to increase infectivity through enhanced membrane fusion activity (Walls et al, 2020; Vankadari, 2020; Xia et al, 2020). Consequently, mutations at these sites can alter virulence—for instance, a recent study reported that mutations disrupting the multibasic nature of the S1/S2 site affect SARS-CoV-2 membrane fusion and entry into human lung cells (Hoffmann et al, 2020).…”
Section: Whole-genome Association Analysis Of the Sars-cov-2 Genomesmentioning
confidence: 99%
“…[4][5] This type of cleavage generates two protein fragments, S1 and S2, of which the former exposes a newly created C-terminal polypeptide chain with the sequence RRAR. 6,7 This amino acid motif allows the S1 protein to interact with other cell surface receptors, such as Neuropilins (Nrps). [1][2][3]8 Eventually S1 and S2 separate, with S2 displaying a membrane fusion domain (which was previously largely hidden by S1 in the structure of the virus Spike protein).…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, molecular analyses of furin bound to protein S of SARS-CoV-2, including MD, docking simulations and functional studies, unveiled the mechanisms of furin binding. It also rationalized the genetic variants, giving important indications for antibody and drug research [ 186 ].…”
Section: Overview Of Some Of the Applications Of Structural Bioinformmentioning
confidence: 99%